Clinical and Magnifying Narrow-Band Imaging Endoscopic Finding–Olmesartan-Associated Collagenous Gastroduodenitis - Desai, Pankaj; Patel, Chintan; Kabrawala, Mayank; Nandwani, Subhash; Arora, Priya; Parekh, Krishna (Journal of Digestive Endoscopy, 2020)
Collagenous gastroduodenitis is a rare and may be associated with olmesartan, an angiotensin–II receptor antagonist used for management of hypertension. It is characterized by marked subepithelial collagen deposition with mucosal inflammatory infiltrate. The characteristic endoscopic finding of collagenous gastritis is nodular mucosa and other findings include erythema friability, erosions, ulcers and atrophy. Olmesartan-associated collagenous gastroduodenitis without colonic involvement is exceptionally rare with only one case reported in literature to date. The association may be difficult to recognize because of its clinical and histologic similarity to the clinical entity collagenous gastroduodenitis. We present a case of Olmesartan-associated collagenous gastroduodenitis, which was observed on magnifying narrow-band imaging endoscopic findings.
Keywords: collagenous gastroduodenitis; M-NBI finding; olmesartan